2023
DOI: 10.1126/science.abq1053
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating mitochondrial electron flow enhances tumor immunogenicity

Kailash Chandra Mangalhara,
Siva Karthik Varanasi,
Melissa A. Johnson
et al.

Abstract: Although tumor growth requires the mitochondrial electron transport chain (ETC), the relative contribution of complex I (CI) and complex II (CII), the gatekeepers for initiating electron flow, remains unclear. In this work, we report that the loss of CII, but not that of CI, reduces melanoma tumor growth by increasing antigen presentation and T cell–mediated killing. This is driven by succinate-mediated transcriptional and epigenetic activation of major histocompatibility complex–antigen processing and present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…5B), which plays a role in the assembly of mitochondrial respiratory chain complex II, aligns with recent research suggesting that complex II deficiency enhances antigen presentation and T cell-mediated killing. 12 In addition, Gene Set Enrichment Analysis (GSEA) demonstrated that TPP-CuET inhibited the cuproptosis target TCA cycle (Fig. 5E), disrupted the mitochondrial inner membrane, and impeded the electron transport chain, thereby substantiating its impact on mitochondrial functions (Fig.…”
Section: Transcriptome Analysis Of Antitumor Mechanismsmentioning
confidence: 89%
See 1 more Smart Citation
“…5B), which plays a role in the assembly of mitochondrial respiratory chain complex II, aligns with recent research suggesting that complex II deficiency enhances antigen presentation and T cell-mediated killing. 12 In addition, Gene Set Enrichment Analysis (GSEA) demonstrated that TPP-CuET inhibited the cuproptosis target TCA cycle (Fig. 5E), disrupted the mitochondrial inner membrane, and impeded the electron transport chain, thereby substantiating its impact on mitochondrial functions (Fig.…”
Section: Transcriptome Analysis Of Antitumor Mechanismsmentioning
confidence: 89%
“…10,11 The latest study by Mangalhara et al shows that enhanced tumor antigen presentation and T cell-mediated killing can be achieved by manipulating mitochondrial electron flow. 12 Therefore, targeting mitochondrial vulnerabilities emerges as a promising therapy model for cancer therapy. Tsvetkov et al discovered that some copper ionophores, like diethyldithiocarbamate, could bind lipoylated proteins of the (tricarboxylic acid) TCA cycle at mitochondria and induce cuproptosis in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively several lines of evidence support the idea that increased oxidative stress supports tumour initiation an metastatisation 26 however this effect is largely dependent on the genetic and metabolic context 10,26 . Furthermore, high ROS levels contribute to the efficacy of many anticancer drugs 12 and increase cancer cell immunogenicity 22,27 . It is clear therefore that fine tuning of ROS levels can tilt the cell balance between life and death.…”
Section: Discussionmentioning
confidence: 99%
“…Manipulating the mitochondrial electron transport chain (ETC) enhances tumor immunogenicity, rendering immune-evasive tumors vulnerable to immune surveillance. Dysfunction of complex II (CII) leads to the abnormal transfer of electrons in the ETC, an increase in succinate production and upregulation of the expression of major histocompatibility complex (MHC) and antigen processing and presentation (APP) genes, making GBM more susceptible to cytotoxic T-cell recognition and elimination. Moreover, mitochondrial DNA (mtDNA) possesses CpG motifs, making them vulnerable to mitochondrial reactive oxygen species (mtROS). , Here, we synthesized iridium photosensitizer (IrPS) that electrostatically bind to GBM cell mitochondria by the positive charge after illumination by two-photon light, induce ETC damage, and produce mtROS to oxidize mtDNA. Oxidized mtDNA in GBM can activate the STING pathway, thereby enhancing GBM immune responsiveness and subsequently activating both innate and adaptive immunity.…”
Section: Introductionmentioning
confidence: 99%